2019
DOI: 10.1016/j.hemonc.2019.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Oncotype Dx recurrence score using clinical parameters

Abstract: Objective/Background: The Oncotype Dx test is a genomic test currently used in clinical practice to predict the risk of disease recurrence in estrogen receptor (ER)-positive, HER2-negative breast cancer patients with axillary lymph node-negative or micrometastatic disease. The test is one of several similar genomically based tests available. Although it has a good predictive value, it is expensive and thus constitutes a significant financial burden for health systems. Thus, several attempts have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 16 publications
3
9
2
Order By: Relevance
“…Similar findings of grade and PR status to be the strongest predictors of RS were reported by Orucevic et al 27 Studies have proposed to rely on grade and PR status to predict the RR and therefore avoid ordering Oncotype Dx assay in ER-positive, HER2-negative, and node-negative tumors, specifically where the resources are limited. 16 Contrary to this, our study revealed a trend toward association for lymph node involvement, and it was observed that RS for cases with no nodal involvement was much higher compared with those with nodes. This may be because, in our sample, the number of cases with positive nodes was 3 times less than that with negative nodes.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Similar findings of grade and PR status to be the strongest predictors of RS were reported by Orucevic et al 27 Studies have proposed to rely on grade and PR status to predict the RR and therefore avoid ordering Oncotype Dx assay in ER-positive, HER2-negative, and node-negative tumors, specifically where the resources are limited. 16 Contrary to this, our study revealed a trend toward association for lymph node involvement, and it was observed that RS for cases with no nodal involvement was much higher compared with those with nodes. This may be because, in our sample, the number of cases with positive nodes was 3 times less than that with negative nodes.…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, the RS for grade 3 cases was more than 2 times that of grade 1, and there was a remarkable decrease in RS as the grade decreased. Thibodeau and Voutsadakis 16 also reported a similar trend with all grade 3 tumors having a high RS compared with grades 1 and 2. The interesting finding in this study was that although negativity of PR status was in inverse correlation to RS, having 1+ staining was associated with higher RS compared with no staining.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Several predictive models for RS have been reported, and age, tumor size, nuclear grade, lymphovascular invasion, histological type, ER, PgR, HER2, and Ki-67 have been reported as clinicopathological factors associated with RS (2,(6)(7)(8)(9)(10)(11). In the present study, we specifically utilized four immunohistochemical markers that are routinely used to determine the intrinsic breast cancer subtype in clinical practice.…”
Section: Discussionmentioning
confidence: 99%